The effectiveness of hydrocolloid dressing in post-operative wound healing: a narrative review - Hastuti, Hediati; Nugraha, Bambang Aditya; Annisa, Hanun Nur; Aprilia, Ilma; Maesaroh, Imas; Karwati, Karwati; Hasna, Lathifah (Institute Of Computer Science (IOCS), 2024)
Hydrocolloid dressings, recognized as advanced wound care solutions, enhance the healing process through their impermeable characteristics. This narrative review aims to evaluate the efficacy of hydrocolloid dressings in managing post-operative wounds. This research scrutinized literature from databases and search engines such as PubMed, Cochrane Library, and Google Scholar, focusing on publications from 2013-2023. Analysis of five selected articles revealed that hydrocolloid dressings not only effectively support the healing of surgical wounds but also offer prolonged usage and cost-efficiency. These benefits underscore the value of hydrocolloid dressings as a recommended practice for post-operative wound care among nurses and healthcare professionals.